Lauric acid modulates the cyclooxygenases and nitric oxide pathways and reduces oxidative stress in preventing tracheal hyperresponsiveness in asthmatic Wistar rats - Figueiredo, Indyra Alencar Duarte; Martins, Alissa Maria de Oliveira; Cavalcanti, Alexya Mikelle Teixeira; Fernandes, Jayne Muniz; Gomes, Ludmila Emilly da Silva; Oliveira, Gabriel Nunes Machado de; Oliveira, Lucas Nóbrega de; Felício, Isabela Motta; Golzio, Adriana Maria Fernandes de Oliveira; Alves, Adriano Francisco; Vasconcelos, Luiz Henrique César; Cavalcante, Fabiana de Andrade (Frontiers in Pharmacology, 2026)
Lauric acid, or dodecanoic acid, a medium-chain fatty acid, prevents alterations in pulmonary ventilation and tracheal hyperresponsiveness in Wistar rats with allergic asthma induced by ovalbumin (OVA). Therefore, the aim was to evaluate the mechanism of action of lauric acid (LA) in its preventive effect on changes caused by asthma. Rats were randomly divided into a control group (CG), an asthmatic group (AG), and an asthmatic lauric acid 25-mg/kg group (ALA25G). Rats in the AG and ALA25G groups were sensitized and challenged with OVA. For the experimental protocols, the trachea and lungs were isolated after euthanasia. A reduction in the contractile reactivity to CCh was observed in the asthmatic group in the presence of indomethacin, zileuton, L-NAME, apocynin, and tempol, inhibitors of COX, 5-LOX, NOS, NADPH oxidase, and a mimetic of superoxide dismutase (SOD), respectively. In the ALA25G, the contractile reactivity was reduced in the presence of indomethacin, L-NAME, and apocynin. Furthermore, an increase in lipid peroxidation (MDA) and nitrite levels and a reduction of reduced glutathione (GSH) levels and SOD activity were observed in the pulmonary homogenate of the AG. Treatment with lauric acid at a dose of 25 mg/kg prevented all of these alterations, except for the reduction in GSH levels. In conclusion, LA reduces tracheal hyperresponsiveness in Wistar rats with allergic asthma by negatively modulating both the COX and NO pathways and oxidative stress imbalance.